우수관망 구조에 따른 유출 속도 분석 - 이진우; 정건희; Lee, Jinwoo; Chung, Gunhui (Journal of Korea Water Resources Association, 2018)
Rainfall falling in the impervious area of the cities flows over the surface and into the stormwater pipe networks to be discharged from the catchment. Therefore, it is very important to determine the size of stormwater pipes based on the peak discharge to mitigate urban flood. Climate change causes the severe rainfall in the small area, then the peak rainfall can not be discharged due to the capacity of the stormwater pipes and causes the urban flood for the short time periods. To mitigate these type of flood, the large stormwater pipes have to be constructed. However, the economic factor is also very important to design the stormwater pipe networks. In this study, 4 urban catchments were selected from the frequently flooded cities. Rainfall data from Seoul and Busan weather stations were applied to calculate runoff from the catchments using SWMM model. The characteristics of the peak runoff were analyzed using linear regression model and the 95% confidence interval and the coefficient of variation was calculated. The drainage density was calculated and the runoff characteristics were analyzed. As a result, the drainage density were depended on the structure of stormwater pipe network whether the structures are dendritic or looped. As the drainage density become higher, the runoff could be predicted more accurately. it is because the possibility of flooding caused by the capacity of stormwater pipes is decreased when the drainage density is high. It would be very efficient if the structure of stormwater pipe network is considered when the network is designed. 도시 지역의 불투수층에 내린 강우는 지표면을 따라 흐르다가 대부분 우수관으로 유입되어 유역에서 배출된다. 그러므로 도시 우수관의 설계빈도를 결정하고 설계홍수량을 결정하는 일은 도시 홍수 저감을 위한 구조적인 대책 중 가장 우선적으로 고려되어야 하고, 또 가장 중요한 대책이기도 하다. 그러나 최근 들어 기후변화 등으로 인해 짧은 시간에 큰 강우강도의 호우가 발생하는 일이 잦아지고 있다. 이런 형태의 호우는 불투수면이 많은 도시 지역에서 갑작스럽게 유출량을 증가시켜 증가된 유출량이 일시에 우수관으로 유입되지 못하고 일시적이고 국부적인 홍수를 야기하기도 한다. 그러므로 도심지의 홍수 저감을 위해 우수관망의 적절한 설계가 매우 중요하다. 그러나 무한정 큰 관경의 우수관을 건설하는 것은 경제적으로 타당한 방법이 될 수 없으므로, 적절한 크기의 우수관을 설계하고 유출해석의 신뢰도를 높이기 위한 노력이 필요하다. 그러므로 본 연구에서는 과거 홍수피해가 빈번히 발생했던 도시유역들 중 유역면적과 우수관망의 구조가 다른 4개의 도시를 서울과 부산지역에 선정하여 다양한 강우에 따른 유출해석을 실시하였다. 서울과 부산 기상관측소의 과거 호우 자료에 대한 EPA-SWMM 모형에서의 유출해석 결과, 첨두강우량의 변화에 따른 첨두유출량의 변화를 선형회귀모형으로 분석하였다. 회귀모형의 결정계수와 95% 신뢰구간 및 변동계수를 비교하고, 수계밀도 개념을 적용하여 첨두유출량의 변화를 해석한 결과, 우수관망이 조밀하게 건설되어 수계밀도가 높을수록 증가된 첨두강우량에 따라 함께 증가하는 첨두유출량의 예측이 상대적으로 정확하게 가능함을 확인하였다. 이는 수계밀도가 높을수록 유출응답이 빨라지고 국부적인 우수관의 통수능 부족으로 발생하는 침수의 발생 가능성이 낮아지기 때문인 것으로 보이며, 갑작스러운 강우에 대한 대응이 수월함을 의미한다. 이러한 우수관의 구조적인 특성에 따른 유출 응답 속도를 고려하여 우수관을 설계한다면, 보다 효율적인 우수관 설계가 가능할 것으로 판단된다.